Liquid Soap Formulation Of Avocado (Persea americana Mill) Fruit Ethanol Extract - Widyastuti, Widyastuti (SITAWA : Jurnal Farmasi Sains dan Obat Tradisional, 2023)
Avocado fruit has activity as an antibacterial and antioxidant and is often used as a cosmetic ingredient. Formulation of avocado fruit extract as a cleaning cosmetic has not been done much. This study aims to formulate the ethanol extract of avocado fruit in the form of liquid soap using palm oil and olive oil. Liquid soap formulation of ethanol extract of avocado fruits uses 55% KOH. Evaluation of the preparations included organoleptic, homogeneity, stability, specific gravity, foam height, pH and determination of free alkali. All preparations met the requirements, except for pH and free alkali.The best formula is given by F2 which contains 10% olive oil.